Człowiek i nieskończoność. O rozwoju i porażce ideologii nicwięcyzmu - Szulakiewicz, Marek (Humaniora. Czasopismo Internetowe, 2023)
We encounter the idea of infinity at an existential, epistemological, and scientific level. Man has the understanding of being finite, and at the same time, this understanding takes him beyond it, towards the infinite. Thereforte, the problems of finitude and infinity have been an enduring philosophical issue. However, this did not just mean trying to get a grasp of it, but to include it in experiencing of the world. Infinity was the condition of possibility for our experience. The inclusion of this idea in our experience meant trying to go beyond this world and discovering another dimension. From the 17th century onwards, its slow loss as a condition of our experience was taking place. The result is an ideology of nothingbutism in which the ‘Fifth Dimension’ (J. Hick) is eliminated. The article shows the dangers of this ideology and its overcoming by modern science and philosophy.